Sport exercise capacity of soccer players at different levels of performance - Andrzejewski, M.; Chmura, J.; Dybek, T.; Pluta, B. (Biology of Sport, 2012)
The aim of the study is to compare the level of exercise capacities to the loads occurring at the lactate threshold among soccer players representing different levels of sport mastery. The research included 51 soccer players representing different levels of sport mastery. The research was conducted at the beginning of the preparatory period for the spring season. A field exercise test of increasing intensity was performed to check the players` exercise capacities on the soccer pitch. The test enabled us to determine the 4 millimolar lactate threshold (TLA 4 mmol/l) on the basis of lactate concentration in blood (LA), and to define the threshold running speed and the threshold heart rate (HR). The lactate level in blood was measured using a Lactate Scout photometer with the enzyme-amperometric method from capillary blood for 20 seconds after each load. The threshold running speed at the level of the 4 millimolar lactate threshold was marked using the two-point form of the equation of a straight line. The conducted tests showed significant differentiation of the threshold running speed among individual teams. The soccer players of a leading first league club were expected to achieve the best result. The conducted tests did not confirm this assumption. Juniors reached the highest threshold running speed of 3.61 m/s. Lower values of the analysed indicator were acquired by players of the first league team (3.50 m/s) and the lowest by players of the second league team (3.28 m/s). Statistically significant differences were noted between the junior group and second league team and between the first and the second league soccer players (p<0.05).